2021
DOI: 10.1016/j.ijheatmasstransfer.2021.120931
|View full text |Cite
|
Sign up to set email alerts
|

Child droplets from micro-explosion of emulsion and immiscible two-component droplets

Abstract: Here we present the experimental findings of the research into the integral characteristics of secondary droplets produced from the micro-explosive fragmentation of two types of initial droplets. Both types are based on water and tetradecane: an emulsion droplet and a two-component immiscible droplet with water as the core and tetradecane as the envelope. We study the threshold (critical) conditions for the microexplosion of droplets on a substrate heated up to 550 °C. In the course of experiments, we recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Research findings [5,112] show that the heating arrangement of initial droplets has a decisive effect on the number and size of secondary fragments produced in the puff-ing and micro-explosion regimes. The maximum number of secondary fragments was recorded [5,112] in experiments where parent droplets were placed on a heated solid surface (with dominant conductive heat transfer), and the minimum number of droplets were produced upon heating in a tubular muffle furnace (with dominant radiative heat transfer). In experiments with dominant convective heat transfer, the authors recorded the average number of secondary fragments compared with other arrangements studied [5,112].…”
Section: Progress In Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings [5,112] show that the heating arrangement of initial droplets has a decisive effect on the number and size of secondary fragments produced in the puff-ing and micro-explosion regimes. The maximum number of secondary fragments was recorded [5,112] in experiments where parent droplets were placed on a heated solid surface (with dominant conductive heat transfer), and the minimum number of droplets were produced upon heating in a tubular muffle furnace (with dominant radiative heat transfer). In experiments with dominant convective heat transfer, the authors recorded the average number of secondary fragments compared with other arrangements studied [5,112].…”
Section: Progress In Mathematical Modelingmentioning
confidence: 99%
“…The maximum number of secondary fragments was recorded [5,112] in experiments where parent droplets were placed on a heated solid surface (with dominant conductive heat transfer), and the minimum number of droplets were produced upon heating in a tubular muffle furnace (with dominant radiative heat transfer). In experiments with dominant convective heat transfer, the authors recorded the average number of secondary fragments compared with other arrangements studied [5,112]. The aspects outlined in the experiments [5,112] can benefit the mathematical models of droplet breakups by controlling for critical heat fluxes at the droplet surface in contact with the heating environment.…”
Section: Progress In Mathematical Modelingmentioning
confidence: 99%
“…Several studies have shown the potential of this emulsified feedstock technique in chemical production. [8][9][10][11] Due to the great potential of micro-explosion application, a large number of researchers have sought to understand its mechanism and regular patterns by exploring and observing the micro-explosion phenomenon of single droplets [12][13][14] . It has been found that there are at least two different forms of micro-explosion in single droplet micro-explosion experiments, namely "micro-explosion" and "puff" 12,[15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Due to the great potential of micro-explosion application, a large number of researchers have sought to understand its mechanism and regular patterns by exploring and observing the micro-explosion phenomenon of single droplets [12][13][14] . It has been found that there are at least two different forms of micro-explosion in single droplet micro-explosion experiments, namely "micro-explosion" and "puff" 12,[15][16][17][18][19][20] . In some studies, these two forms of micro-explosion are also called "optimal micro-explosion" and "non-optimal micro-explosion" respectively 6,7,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The latest experimental studies focused on the relationship between the size of secondary droplets and the temperature of the water core and the influence of additives in droplets on the formation of secondary droplets. The numerical studies focused on the droplet nucleation temperature of the heating rate and the influence of puffing/microexplosion time. , Meng et al observed secondary droplets caused by the secondary explosion of the jet fuel (RP-3), biodiesel, and ethanol-mixed droplets. The calculation equation of the microexplosion intensity was established to assess the degree of secondary droplet ejection.…”
Section: Introductionmentioning
confidence: 99%